Determinants of Regional Budget Realization Supervision in the West Halmahera Regency DPRD: (Study on the DPRD of West Halmahera Regency) - Naswan Hadilia; Aspiati A. Samiun (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
This research uses a quantitative descriptive approach. The sampling technique used a saturated census (total sampling), as well as the data analysis method using multiple linear regression analysis. The objectives of this study are: (1) To determine and analyze the influence of the personal and political backgrounds of DPRD members on the supervision of the realization of the West Halmahera Regency Regional Budget (APBD). (2) To determine and analyze the influence of the organizational commitment of DPRD members on the supervision of the realization of the West Halmahera Regency Regional Budget (APBD). (3) To determine and analyze the influence of DPRD members' budget knowledge on the supervision of the realization of the West Halmahera Regency Regional Budget (APBD). The results of this study indicate that: (1) Personal and political backgrounds do not have a positive and significant influence on the supervision of the realization of the West Halmahera Regency Regional Budget (APBD). (2) Organizational commitment has a positive and significant influence on the supervision of the realization of the West Halmahera Regency Regional Budget (APBD). (3) Budget knowledge has a positive and significant influence on the supervision of the realization of the West Halmahera Regency Regional Budget (APBD).